Economic Rotation of Sissoo Tree Plantations (Strip) in Bangladesh - Yunus, Mohammad; Hossain, M. A. T; Yasmin, Farzana; Milon, MD (Asian Journal of Agriculture and Rural Development, 2014)
The paper elaborately discusses the various economic rotation methods of sissoo (Dalbergia sissoo) plantations in Bangladesh. Under the present management system, mode of marketing, market mechanism and all the economic criteria for Bangladesh as a whole, the economic rotation of sissoo tree may be fixed at 8 year for fuel wood and 12 or 13 year for timber. But if the Mean Annual Increment (MAI) is considered as rotation criterion, rotation age as 6 year for fuel wood and 11 to 13 year for timber may be suggested. The elimination rates varied from 10% to 72% depending on plantation year and location. It was found 10% in the area of Jessore and more than 50% in Rajshahi, Jessore and Dinajpur. For 6th year plantation the IRR was found highest (39%) in Mymensingh. The 14th year plantation of Rajshahi and 13th year plantation of Jessore showed the highest NPVs, IRRs, B/C ratios, Le, EI and EAEnpv. From these, it can be inferred that the economic rotation may be fixed at 13 or 14 year for timber and 6 year for fuel wood.